Hair mercury level of coastal communities in Malaysia: a linkage with Fish consumption - Hajeb, Parvaneh; Selamat, Jinap; Ahmad, Ismail; Abu Bakar, Fatimah; Bakar, Jamilah; Lioe, Hanifah Nuryani (2008)
Hair mercury level was assessed in four coastal communities in Malaysia with relation to fish consumption between gender, age, and rural and urban area. Mercury level was found at a range of 0.01–21.00 (g/g dry wt). The average mercury levels were 13.69, 10.85, 9.94, and 6.78 g/g dry wt for communities in Kedah, Terengganu, Johor, and Selangor, respectively. The same order was found for the average monthly Wsh consumption, that is 14,620 § 878, 9,966 § 563, 8,939 § 793, and 8,169 § 658 g/month for communities in the four respective regions. A highly significant positive correlation between hair mercury concentration and fish consumption was observed in all communities. This gives an insight that fish consumption is a significant route of mercury exposure for the coastal communities.Females had higher hair mercury concentration than what males had. Mercury exposure of communities in rural area was higher when compared to that in urban. However, mercury level in all Malaysian communities studied was much lower than no observable adverse eVect level (NOAEL) of WHO, that is 50 mg/g dry wt.